EFEKTIVITAS MENGENAI KEPASTIAN HUKUM PENERAPAN DELIK FORMIL UU 20/2001 TENTANG PEMBERANTASAN TIPIKOR (25/PUU-XIV/2016) - Tador Christopher D.H.; Firman Wijaya (Jurnal Hukum Adigama, 2019)
Decision of the Constitutional Court Number 25/PUU-XIV/2016 has ruled that the use of the phrase "can" in Article 2 paragraph (1) jo. Article 3 of the UU Tipikor has been declared contrary to the UUD NRI 1945 and declared contrary to the law. However,Decision No. 25/PUU-XIV/2016 basically contrary to Legal Certainty. The problem examined is how is the legal certainty in the application of formal offense in the elimination of the "can" in Article 2 Paragraph (1) Jo Article 3 of the UU Tipikor after Post-Corruption The Constitutional Court of the Republic of Indonesia Number 25 / PUU-XIV / 2016 which Changes the Application of the Form of Formal Decree into Material Delict? The author examines this problem using normative research methods supported by expert interview data. The author analyzes that in removing the word "can" from the formulation of the two norms of the article will fundamentally change the offense qualifications of criminal acts of corruption. The author concludes that the Decision was basically inappropriate, because it contradicted Legal Certainty. The author suggests that there needs to be an affirmation of the Decision and the Judge in deciding the Decision should review the contents of the Decision Number 003/PUU-IV/2006 which is a form of jurisprudence.